Native-Valve Aspergillus Endocarditis: Case Report and Literature Review - Claudio Caroselli; Lorenzo Roberto Suardi; Laura Besola; Alessandro Fiocco; Andrea Colli; Marco Falcone (MDPI AG, 2023)
Aspergillus endocarditis represents the second etiological cause of prosthetic endocarditis following Candida spp. On the other hand, native-valve endocarditis due to Aspergillus are anecdotally reported with increasing numbers in the last decade due to new diagnostic technologies such as polymerase chain reaction (PCR) on samples like valve tissue or entire blood. We performed a review of the literature presenting one case report observed at Pisa University Hospital. Seventy-four case reports have been included in a period between 1950-2022. Immunocompromised status (patients with solid tumor/oncohematological cancer or transplanted patients) was confirmed to be the main risk factor for this rare opportunistic infection with a high rate of metastatic infection (above all, central nervous system) and mortality. Diagnosis relies on serum galactomannan and culture with PCR on valve tissue or whole blood. Cardiac surgery was revealed to be a life-saving priority as well as appropriate antifungal therapy including b-liposomal amphotericin or new triazoles (isavuconazole). The endocarditis team, facing negative blood culture endocarditis affecting an immunocompromised patient, should investigate this difficult-to-treat pathogen.